DIRECTIVE ACTS FORM IN LINDA PRESS WULF’S NOVEL “The Night of the Burning” - Fitria Putri Piskasari; Siti Nuraeni; Intan Sukma Irani; Yesika Maya Ocktarani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Communication is an important aspect in the social life. They use language as means of communication to havegood interaction. Sometimes, when a message is needed to be express by someone, the form of the expression can be varied. It can be direct and indirect. From this form, someone express what they want and feel to theirhearer, therefore through their utterance, the hearer do something for them. An act that appears because of thespeaker’s utterance is called as Speech Acts. Speech Acts classified into five kinds and this research focuses onDirective Speech Acts (DSA). This research analysed the DSA form in literary work, The Night of the Burning.The aim of this research to identify the form of DSA in The Night of the Burning novel, therefore the researcher used Austin and Searle theory for speech acts, also Birner theory to DSA forms. The data were collected by using taking note and library method. This research shows that there are two forms of DSA that found in this novel. There are Direct and Indirect Speech Acts. Communication is an important aspect in the social life. They use language as means of communication to have good interaction. Sometimes, when a message is needed to be express by someone, the form of the expression can be varied. It can be direct and indirect. From this form, someone express what they want and feel to their hearer, therefore through their utterance, the hearer dosomething for them. An act that appears because of the speaker’s utterance is called as Speech Acts. SpeechActs classified into five kinds and this research focuses on Directive Speech Acts (DSA). This research analysedthe DSA form in literary work, The Night of the Burning. The aim of this research to identify the form of DSA in The Night of the Burning novel, therefore the researcher used Austin and Searle theory for speech acts, also Birner theory to DSA forms. The data were collected by using taking note and library method. This research shows that there are two forms of DSA that found in this novel. There are Direct and Indirect Speech Acts.. Keywords: Directive Speech Acts, Literary Work, Direct and Indirect Speech Acts